2015
DOI: 10.1186/s12981-015-0055-x
|View full text |Cite
|
Sign up to set email alerts
|

Determination of HIV-1 coreceptor tropism using proviral DNA in women before and after viral suppression

Abstract: BackgroundAn HIV-1 tropism test is recommended prior to CCR5 antagonist administration to exclude patients harboring non-R5 virus from treatment with this class of antiretrovirals. HIV-1 tropism determination based on proviral DNA (pvDNA) may be useful in individuals with plasma viral RNA suppression. We developed a genotypic tropism assay for pvDNA and assessed its performance in a retrospective analysis of samples collected longitudinally.ResultsWe randomly selected paired plasma/PBMC samples from the Women’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
1
3
0
Order By: Relevance
“…The small cohort size was composed of two groups of comparable numerosity and immuno-virological characteristics at BL and this is a strength of the study. The percentage of subjects with a X4 tropic virus infection at BL is high (42.9%) but comparable to that reported in previous studies in patients on successful ART 13 , 47 , 48 and possibly influenced by the immune activation state 49 .…”
Section: Discussionsupporting
confidence: 86%
“…The small cohort size was composed of two groups of comparable numerosity and immuno-virological characteristics at BL and this is a strength of the study. The percentage of subjects with a X4 tropic virus infection at BL is high (42.9%) but comparable to that reported in previous studies in patients on successful ART 13 , 47 , 48 and possibly influenced by the immune activation state 49 .…”
Section: Discussionsupporting
confidence: 86%
“…The use of proviral DNA from PBMC for co-receptor determination (an approach that still has to be validated) may be a limitation of the current study. However, a number of studies, employing Sanger sequencing, have shown a strong correlation in co-receptor preference prediction between HIV variants obtained from plasma and PBMC [43][44][45][46].…”
Section: Discussionmentioning
confidence: 99%
“…Co-receptor tropism was inferred with the geno2pheno algorithm setting the false positive rate (FPR) at 10% for plasma samples and 20% for PBMC samples, [ 1 ] based on previous studies [ 28 , 29 ] showing concordant results in the determination of co-receptor tropism for the same individual whether plasma RNA or proviral DNA was used. Co-receptor tropism for all PD patients was determined only on plasma RNA at either time-point; similarly in PU patients, co-receptor tropism was assessed only on proviral DNA at either time-point.…”
Section: Methodsmentioning
confidence: 99%